Lexical and syntactic markers of small literary genres - Nadezhda Bujlova; Olga Lyashevskaya (Вестник Православного Свято-Тихоновского гуманитарного университета: Сериа III. Филология)
This article presents a case study of surface syntax constructions of Russian verbs with respect to their use in various genres of fi ction. The article primarily deals with verb complementation and constructions with adjuncts, as well as with lexical constraints on the construction slots. Five types of dependency relations are taken into consideration, i.e. subject, direct and oblique object, infi nitive clause, and adverbial clause. The prototypical constructions of the verb complementation are mapped to reduced and extended constructions, other changes such as an ellipse in a subordinate group, and to actant derivations motivated by the specialisation of the lexical sense of the verb in a particular genre. In order to identify constructions for the analysis, we used the Random Forest classifi cation method and calculated the metric of importance for the surface syntax verb constructions. The article also outlines the constructional portraits of four small genres, i.e. detective stories, romance novels, fantasy, and science fiction. It is shown that the topics, the structure of the narrative, the authors’ use of cliches, the way how the text follows the literary trends aff ect not only the choice of vocabulary, but also the constructional potential of the verb. In general, the article provides a starting point for studying the interaction of lexicon, semantics, and syntax at the level of microgenres in fi ction. The data obtained can be used in models of automatic text classifi cation for electronic libraries.